(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional and radiological outcome of our newly designed an innovative Pin Locked Kuntscher Intrameduallry Nailing (PLKIN) construct for Femoral Shaft Fractures. Methods: This descriptive study was conducted in Millat Orthopedic and Trauma Surgery Hospital Sargodha- from 23rd February 2019 to 23rd May 2022.All patients with femoral shaft fractures fulfilling the inclusion criteria were treated with our indigenously designed innovative PLKIN construct. The final radiological outcome of PLKIN was determined at two years of follow up by assessing fracture healing. The functional outcome was assessed with Thorensen’s criteria and graded as excellent, good fair and poor outcome. Results: We treated 19 patients with PLKIN construct. The mean age was 36.74±3.11 years. Male patients were 13(68.42% ) and females were 6( 31.57%).Right sided femoral fracture was present in 11( 57.89%) patients and left in 8(42.10% ) patients. At two years follow up union was achieved in all 19 patients without additional surgeries. Excellent functional outcome was noted in 14(73.68%) patients and good in 5( 26.31%) patients. Conclusion: Our newly designed innovative Pin Locked Kuntscher Intrameduallry Nailing (PLKIN) construct is an effective device for the treatment of selective femoral shaft fractures as shown by excellent functional and radiological outcome in majority of our patients. We therefore recommend PLKIN construct a suitable alternative to conventional Kuntscher intramedullary nails and interlocking nails for treating femoral shaft fractures.